Prevalence and Antimicrobial Resistance of Bacterial Uropathogens Isolated from Iranian Kidney Transplant Recipients: A Systematic Review and Meta-Analysis - Abbas SHAPOURI MOGHADDAM; Maryam ARFAATABAR; Jalil TAVAKOL AFSHARI; Ali SHAKERIMOGHADDAM; Zahra MOHAMMADZAMANI; Azad KHALEDI (Tehran University of Medical Sciences, 2019)
Background: Urinary tract infection (UTI) is a major complication in patients who receive the kidney transplant. We aimed to evaluate the prevalence and antimicrobial resistance of bacterial uropathogens isolated from Iranian kidney transplant recipients. Methods: We searched according to Prisma protocol for UTI infection, prevalence, occurrence and distribution of bacteria and their pattern of antibiotic resistance among Iranian patients who receive kidney transplant through online electronic databases with MeSh terms and text words in published references in both Persian and English languages during 1990-2017. Data analysis was performed using Comprehensive meta-analysis software (CMA) by Cochrane Q and I2 Random Effects Model. Results: Eleven studies met the eligible inclusion criteria. The prevalence of UTI among kidney transplant patients varied from 11.7% to 67.5%. The combined prevalence of UTI was 32.6%. Among Gram-negative pathogens causing UTI, E. coli was the most dominant followed by Klebsiella pneumonia with prevalence 41.3% and 11.9%, respectively. Also, amongst Gram-positive bacteria, the highest prevalence belonged to Enterococcus spp. (9.8%) and coagulase-negative Staphylococci (9.4%). Also in Gram-negative pathogens, the most resistance was to ampicillin (91.2%), followed by ceftazidime (89.5%).  The minimum resistance was against imipenem with prevalence 14.3%. Conclusion: The combined prevalence of UTI was 32.6%. Gram-negative pathogens especially E. coli were the most agents of UTI in Iranian patients who receive kidney transplant. Also, in gram-negative pathogens, the most resistance was to ampicillin that it needs a new strategy for prophylaxis and treatment of UTI after the kidney transplant.